Transparency in Extractive Industries - Wolfowitz, Paul (2016)
Paul Wolfowitz, President of the World Bank, discussed the fight against poverty during the last 20 years, during which East Asian countries have made progress, but Sub-Saharan African poverty has doubled. Oil revenues far exceed official development assistance. Yet for some countries it has been more of a curse than a blessing. Corruption and waste has led to distorted economies and demoralized societies in which government power has become an object of plunder leading to civil war and social chaos. The Extractive Industries Transparency Initiative (EITI) aims to improve governance in resource-rich countries through disclosure and verification of company payments and government revenues from oil, gas, and mining. It focuses on transparency, which is one important aspect of governance—but it is an important step towards transforming resources into real development impact, to real effect on the lives of the poor. He spoke about EITI process still facing many challenges ahead. If EITI is to succeed, it must engage every group that has a stake in the country’s future. EITI process requires governments to significantly increase their capacity while coping with other pressing demands. Making EITI succeed means going beyond just EITI in making revenues more transparent. We need to begin a vigorous effort in the area of helping countries recover stolen assets. For most countries EI revenues by themselves will not be enough by themselves to guarantee higher living standards for all citizens. We must do everything we can to help these countries transform their wealth into a brighter future for every citizen.